EFFECT OF HUMAN ADIPOSE-DERIVED STEM CELL IN COLLAGEN GEL ON RELATIVE EXPRESSION LEVEL OF VASCULAR ENDOTHELIAL GROWTH FACTOR-A OF DEEP DERMAL BURN HEALING - Sari, Puji; Septiara, Dwi Pratami; Junaidi, Helsy; Yunaini, Luluk; Pawitan, Jenanne A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this research was to measure the relative expression levels of vascular endothelial growth Factor-A (VEGF-A) in the deep dermal burns treated with human adipose-derived stem cell (hADSC) in collagen gel in each observational day (days 7, 14, 21, and 28). Methods: This study used 20 male Sprague Dawley rats, divided into four groups of observation days. Each rat received three burn injuries and then given different treatments (hADSC in collagen gel, collagen gel, and control). Deep dermal burn injury on the dorsal was made by placing a metal plate with 250°C for 15 s. Relative expression level of VEGF-A measurement with quantitative reverse transcription polymerase chain reaction. Results: On the 7th day, the relative expression level of VEGF-A in the wound treated with hADSC in collagen gel was significantly different from the scaffold collagen and control group (p<0.05), whereas the control and scaffold collagen group was not significantly different. The relative expression level of VEFG-A in wound treated with hADSC in collagen gel, collagen gel only, and control was (mean±standard error of the mean) 17.93±4.37, 7.54±2.63, and 5.44±1.59, respectively. On the next observation days, the result showed that the relative expression level of VEGF-A was not significantly different between the three treatments. The relative expression level of VEGF-A has decreases from day 7 to 28 days. The decrease of VEGF-A relative expression level hADSC in collagen gel group was significantly different on the 7th day to the 21st and 28th days (p<0.05). Conclusion: The provision of hADSC in scaffold collagen increases the relative expression of VEGF-A early in the wound healing process compared to the without a hADSC group.